Cation assisted binding and cleavage of dinitrogen by uranium complexes. Issue 32 (22nd July 2022) - Jori, Nadir; Rajeshkumar, Thayalan; Scopelliti, Rosario; Z̆ivković, Ivica; Sienkiewicz, Andrzej; Maron, Laurent; Mazzanti, Marinella
Abstract : N2 binding affinity decreases markedly in a series of isostructural U(iii )–alkali ions complexes with increasing cation size. N2 binding is undetectable in the Cs analogue, but the first example of cesium-assisted N2 cleavage to bis-nitride was observed at ambient condition. Abstract : The role of alkali promoters in N2 cleavage by metal complexes remains poorly understood despite its relevance to the industrial production of ammonia from N2 . Here we report a series of alkali bound-oxo-bridged diuranium(iii ) complexes that provide a unique example of decreasing N2 binding affinity with increasing cation size (from K to Cs). N2 binding was found to be irreversible in the presence of K. A N2 complex could be isolated in the solid state in the presence of the Rb cation and crystallographically characterized, but N2 binding was found to be reversible under vacuum. In the presence of the Cs cation N2 binding could not be detected at 1 atm. Electrochemical and Computational studies suggest that the decrease in N2 binding affinity is due to steric rather than electronic effects. We also find that weak N2 binding in ambient conditions does not prevent alkali assisted N2 cleavage to nitride from occurring. More importantly, we present the first example of cesium assisted N2 cleavage leading to the isolation of a N2 derived multimetallic U/Cs bis-nitride. The nitrides readily react with protons and CO to yield ammonia, cyanate and cyanide.